Biodiesel Production from Chicken Fat Using Tetrahydrofuran - Falentina Fransiska (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Biodiesel is produced from transesterification process with vegetable oil or animal fats and methanol as reactans. However insolubility of methanol in oil resulted in long reaction time. To improve the process, co-solvent was used to increase the solubility of methanol in oil. In this study, chicken fat was used as feedstock for biodiesel production through transesterification reaction. The reaction of chicken fat used tetrahydrofuran as co-solvent, NaOH as catalyst, and methanol as reactant at a ratio of methanol to oil 6:1. Variables studied were reaction temperature, reaction time, ratio of co-solvent to methanol, and amount of catalyst. The products of reaction were analyzed by gas chromatography to obtain the composition of biodiesel. The biodiesel properties like methyl-ester content, density, flash point, and viscosity was evaluated and was found to compare well with Indonesian Biodiesel Standard (SNI). The best result was obtained by using 0,5:1 ratio of co-solvent to methanol (v/v), at 50oC, for a reaction time 15 minutes, in the presence 0,8 wt% of catalyst. The results of this work showed that the use of chicken fat is very suitable as low cost feedstock for biodiesel production.